Personality’s Self-Worth as a Resource Process and State - Олена Штепа (Проблеми сучасної психології, 2023)
The aim of the article is to characterize the resource content of a personality’s sense of self-worth in empirical way. Methods. The study was implemented according to Bayer’s model, which involves transforming the problem into the form in which it will have a solution, and enables the practical application of the results. In the empirical study, ten psychological questionnaires were used, which made it possible to determine the following types of psychological resources of a person in empirical way: personal resources, interpretive psychological resources, existential resources, “strengths of character” resources, motivational resources, resources of the psychological survival, uncertainty tolerance resources, resources of relationship, coherence. The sense of self-worth was empirically determined according to the “self-worth” scale of the Existence Scale method by A. Lengle. The following methods of mathematical and statistical analysis were applied: predictor analysis and analysis of “causes and effects” to characterize self-worth as a process, multifactor and cluster analysis as a state. Research results. According to the analysis of predictors, self-worth trends are determined by two resources – the psychological resource of “responsibility” and the existential resource of “belief”; according to the results of the analysis of “causes and effects”, self-worth is the effect of two resources – the psychological resource of “responsibility” and the existential resource of “belief”; the structural resource model of self-worth is three-factor: factor 1 – resources of “strengths of character”, “desire to be involved in a common cause” and “sensitivity in relationships”; factor 2 – interpretive psychological resources of “the intention of wisdom”; factor 3 – existential resource of “belief”; according to the results of the cluster analysis, the sense of self-worth and the existential resource of faith belong to the same cluster. Conclusions. The study’s results make it possible to confirm self-worth empirically as an existential reality of the personality, manifested in the ability to be free and make choices according to one’s values and beliefs. The phenomenon of self-worth should be characterized not only through its importance in the achievement of virtues by a person but because of explanation of the reasons for predicting one’s own harmony. The resource content of self-worth makes it possible to characterize it as a process of self-discovery and reinterpretation of the meaning of events, enabling non-repetition of decisions recognized as erroneous and a state of free choice.